Sugarcane Bagasse: Challenges and Opportunities for Waste Recycling - Hiranobe, Carlos T. [UNESP]; Gomes, Andressa S. [UNESP]; Paiva, Fábio F. G.; Tolosa, Gabrieli R. [UNESP]; Paim, Leonardo L. [UNESP]; Dognani, Guilherme [UNESP]; Cardim, Guilherme P. [UNESP]; Cardim, Henrique P. [UNESP]; dos Santos, Renivaldo J. [UNESP]; Cabrera, Flávio C. [UNESP] (MDPI, 2024)
Sugarcane has primarily been used for sugar and ethanol production. It creates large quantities of residual lignocellulosic biomass such as sugarcane bagasse, leaves, tops, and vinasse. Biomass is a sustainable prospect for biorefineries aiming to optimize production processes. We detail recent research developments in recycling sugarcane, including energy generation and pyrolysis to obtain biofuels, for example. To produce biochar, the energy cost of operating at high temperatures and large-scale production remain as obstacles. The energy generation prospects can be enhanced by pellet production; however, it requires an improvement in quality control for long-term storage or long-distance transportation. In civil construction, the materials still need to prove their long-term efficiency and reliability. Related to adsorbent materials, the use of sugarcane bagasse has the advantage of being low-cost and environmentally friendly. Nevertheless, the extraction, functionalization, and modification of cellulose fibers, to improve their adsorption properties or even mode of operation, still challenges. The synthesis of nanostructures is still lacking high yields and the ability to scale up. Finally, controlling dispersion and orientation and avoiding fiber agglomeration could improve the mechanical response of composites using sugarcane bagasse. The different possibilities for using sugarcane and its residues reinforce the importance of this material for the industry and the global economy. Thus, the present work addresses current challenges and perspectives of different industrial processes involving sugarcane aiming to support future research on waste-derived subjects.
Keywords: biochemicals; biofuels; biomass; biosorbents; composites; contaminants; dietary products; nanocellulose; silica; sugarcane bagasse